Comparing the efficiency of regional knowledge innovation and technological innovation: a case study of China - Shi, Zhen; Wu, Yingju; Chiu, Yung-ho; Shi, Changfeng; Na, Xiaohong (Technological and Economic Development of Economy, 2022)
The combination of knowledge innovation and technology innovation provides vitality for social science and technology innovation. China leaps into the front ranks of the world in the 2021 Global Innovation Index (GII). Therefore, this research takes China’s theoretical-application innovation as the research object and empirically analyzes measure the innovation efficiency of knowledge innovation dominated by universities and technological innovation dominated by enterprises in China, as well as the gravity-center migration trajectory. The results show that the ranking of overall efficiency of theoretical innovation-application innovation is eastern region > central region > western region. Knowledge innovation presents a drag on overall efficiency, while technology innovation offers a contribution to overall efficiency. In the analysis of PIE (R&D personnel of industrial enterprises above a designated size) variables, the efficiency value is relatively low. The peak value of kernel density increases in the eastern, central and western regions, namely the concentration degree of theoretical innovation-application innovation efficiency in China has risen. The gravity center of each stage migrates to the eastern region, meaning the efficiency value of China’s theoretical innovation and application innovation increases more significantly in the eastern region. From the perspective of knowledge innovation and technology innovation, this paper puts forward suggestions for China and provides some references for other developing countries. First published online 10 August 2022